Kesedaran metafora dan pengingatan kosa kata (Jurnal Bahasa, 2001)
Various figurative expressions can often be traced back to a common metaphoric theme or source domain. The present article reports three EFL experiments which indicate that a lexical organization along such metaphoric themes or source domains can facilitate retention of unfamiliar figurative expressions. In view of these findings, the article proposes classroom activities aimed at enhancing language learners' metaphor awareness and at turning this into an additional channel for vocabulary acquisition.